Elections in African Developing Democracies - Miezah, Hilary (Springer International Publishing, 2018)
The book explores the organization, conduct and supervision of elections in emerging democracies. It covers the broad spectrum of the democratic electoral process. This project is a synthesis of the author's practical knowledge and experience in the management of elections with the United Nations and other international organizations in Africa and Asia. The author addresses election practitioners, political parties, and all other stake holders, and provides a vision for building and blending indigenous traditions and systems of election into universally accepted norms and practices.